Lessening The Cost of Whistleblowing Through Hierarchy Peer-Reporting Type: A Grid-Group Cultural Theory Perspective - Hakami, Akhmad Hafizh; Hakim, Tito IM. Rahman; Muhammad, Erfan (Universitas Negeri Padang, 2024)
Purpose – This study examines the moderating effect of peer-reporting type on the influence of microsocial ethical environment, anonymous reporting channel, and perceived personal cost on internal whistleblowing intentions.Methodology – This paper is an empirical study using accounting students at Trunojoyo Madura University and Bahaudin Mudhary University as respondents. By distributing an online questionnaire and using incidental sampling, 156 responses were obtained. WarpPLS software version 7.0 is used to test the hypotheses.Findings – Microsocial ethical environment and perceived personal costs have a significant effect on whistleblowing intentions. Anonymous reporting channel do not have a substantial impact on whistleblowing intentions. Peer-reporting type moderates the influence of anonymous reporting channel on whistleblowing intentions. Still, it does not significantly moderate the effect of microsocial ethical environment and the impact of perceived personal costs on whistleblowing intentions. This research also provides empirical evidence that the hierarchical dimension is a suitable policy to use to report wrongdoing among accounting students at Trunojoyo Madura University and Bahaudin Mudhary University who take forensic accounting courses.Originality – This study is among the earliest to investigate the moderation effect of peer-reporting type. A previous study based on grid-group cultural theory proposes peer-reporting type as one of the antecedents of whistleblowing intentions, albeit at the conceptual level. The present study tries to further develop this concept (peer-reporting type) as a moderating variable by transforming the peer-reporting type concept into a research instrument. Limititation/Implication – The peer-reporting type questionnaire in this research was created referring to the peer-reporting type concept proposed by the previous study. This instrument is based on the four-dimensional concept of grid-group cultural theory, which is still at the conceptual level. Therefore, the validity and reliability of this instrument need to be tested further through settings, respondents, and others research.